Closed and Open Reduction of Nasal Fractures. Issue 1 (January 2020) - James, Joanne Grace; Izam, Azza Shafiqah; Nabil, Syed; Rahman, Normastura Abd; Ramli, Roszalina
Abstract : Aim: The objective of this review was to determine the different types of surgical intervention in the management of nasal bone fractures, the outcomes, and complications associated with each intervention. Methods: A search was conducted using the PubMed and Cochrane Database of Systematic Review databases from January 1, 1997 until September 9, 2017. The search strategy was constructed using the Population Intervention Comparison Outcome framework with keywords related to nasal fracture and its treatment. Two sets of independent researchers performed the analysis. Qualitative analysis was performed using the Methodological Index for Non-Randomized Studies and National Institute for Clinical Excellence methodology for randomized controlled trial checklists. Results: The 4276 titles were obtained from PubMed database alone. Exclusion was made based on the title, abstract and full-text analysis. Finally, 23 papers were included and analyzed. Of the 23 papers, 13 (56.5%) were retrospective record review, 2 (8.7%) were randomized clinical trial or a randomized study and 8 case series (34.8%). 16 (69.6%) studies addressed closed reduction, 3 studies (13%) on open reduction and 4 studies (17.4%) addressed both open and closed reduction. The main focus in the outcome in all studies was accuracy of the anatomical reduction of the nasal bones. Three studies (13.0%) reported restoration of function such as breathing comfort or release in respiratory obstruction and another 3 (13.0%) addressed both cosmetic and breathing outcomes. Residual deformity was the most described complications in the studies (30.4%). In general, most of the studies were not of high quality as they lacked in some key elements in the Methodological Index for Non-Randomized Studies checklist. Conclusion: Both closed and open reduction provided good outcomes in cosmetic and breathing. Septoplasty is recommended to be performed simultaneously with fracture reduction. Abstract : Supplemental Digital Content is available in the text